FORMATION OF ECOLOGICAL THINKING AMONG THE UNIVERSITY GRADUATES, NAMELY FUTURE PROFESSIONALS AND LEADERS - E. I. Khabarova; S. V. Nikitina; L. L. Budaeva (Российский технологический журнал)
The transition to sustainable development requires rejecting unsustainable patterns of production and consumption, it demands that environmental protection policy should be raised to state level. One of the central causes of the ecological crisis is a consumer's attitude to nature. We now realize that market interests are often opposite to the humanitarian interests of citizens in social and environmental security. The attitude to the issues of environmental protection is becoming a permanent component of the management system. Even the ordinary staff of the enterprise has to realize fully the responsibility and obligations for preservation and protection of a favorable ecological situation. Thus, the correlation of economic and ecological interests, only a strictly scientific approach to the industrial technological development can be reached by environmental education of society and professionals. That is why the authors focus on the importance of Foundation of culture for environmentally sustainable production and consumption primarily for the future specialists. The basis for the formation of an ecologically oriented worldview of people can be laid by General and continuous ecological education. It is necessary to give an initial impulse and to teach "to catch up" with the student promptly "running away" technological organization of life. For training of new generation of engineers at leading universities of the world the new principle of the innovative educational environment is implemented: concept of CDIO (Conceive, Design, Implement, Operate). Ecological education in Russia is a set of elements of education and training of all segments of the population today. As a result the following chain is built: ecological education, professional competence, ecological culture. Professional competence of the modern competitive specialist and the head of an enterprise suggests systemic functional knowledge on environmental issues and formed ecological thinking. The possibility of further existence of a civilization depends on competence of today's students.